Water reports N.11 - FAO (FAO, 1997)
These guidelines have been prepared as a result of the expert consultation. Their scope is to draw attention to the problem of seawater intrution into coastal aquifers and to present measures, both legal and technical, to be taken with the view to studing, monitoring, preventing and controlling seawater intrusion. It should appeal both to the authorities responsible for groundwater management and to the decision-makers